On the momentum toward vaccine self-sufficiency in the BRICS: an integrative review of the role of pharmaceutical entrepreneurship and innovation - Zhang, Yongqiang; Li, Hongbo; Xu, Xinglong; Antwi, Henry Asante (Frontiers in Public Health, 2023)
Background With the perspicuous effect of COVID-19 on vaccine demand, academic and business interest in vaccine production in the BRICS has reached its crescendo. Aware of a “dark” past when the BRICS depended heavily on vaccines and pharmaceuticals from other parts of the world, the academic curiosity on how the BRICS have leveraged vaccine self-sufficiency and become the hub of global vaccine production and supply are justifiable, especially in times of ineffable pandemics. Methods The articles were searched from November 2020 to December 2022. Within this period, an electronic search of 13 reputable healthcare and public databases was searched.The initial searches from the designated databases yielded a total of 3928 articles. Then removed duplicated studies through a two-step process and excluded articles without titles and abstracts, and the remaining 898 articles that met the qualification assessment criteria were evaluated for article quality. Results The main entrepreneurial innovations that have quickened the pace of vaccine self-sufficiency in the BRICS includes investment in artificial intelligence (AI) , Big Data Analytics and Block chain technologies. These help to speed the drug delivery process by enhancing patient identification or optimizing potential drug candidates for clinical trials and production. Conclusion Over the past 20 years, the BRICS nations—Brazil, the Russian Federation, India, China, and South Africa—have achieved major strides in vaccine development, regulation, and production. The creation of the BRICS Vaccine Research and Development (R&D) Center will have a significant impact on vaccine cost and accessibility given the anticipated development of stronger research capability, production, and distribution technology, as well as stronger standardization to improve vaccine production quality in the near future. It is anticipated that the BRICS' contributions to vaccine development would alter the global vaccination market and hasten the availability of vaccinations in developing nations. The challenge is turning these hopes into concrete plans of action and outcomes.